JIMD reports-- case and research reports 2011/1 - SpringerLink (Online service).; Society for the Study of Inborn Errors of Metabolism (Berlin New York Springer London SSIEM, 2011)
"JIMD Reports" publishes case and short research reports in the area of inherited metabolic disorders. Case reports highlight some unusual or previously unrecorded feature relevant to the disorder, or serve as an important reminder of clinical or biochemical features of a Mendelian disorder.
Psychosocial Aspects of Predictive Genetic Testing for Acute Intermittent Porphyria in Norwegian Minors -- Enzyme Replacement Therapy and Extended Newborn Screening for Mucopolysaccharidoses: Opinions of Treating Physicians -- Mutation Spectrum of Fumarylacetoacetase Gene and Clinical Aspects of Tyrosinemia Type I Disease -- Generalized Arterial Calcification of Infancy: Fatal Clinical Course Associated with a Novel Mutation in ENPP1 -- Lymphoblastoid Cell Lines for Diagnosis of Peroxisome Biogenesis Disorders -- First Report of a Molecular Prenatal Diagnosis in a Tunisian Family with Lysinuric Protein Intolerance -- Foot Process Effacement with Normal Urinalysis in Classic Fabry Disease -- Growth Hormone Therapy Is Safe and Effective in Patients with Lysinuric Protein Intolerance -- Outcomes of Phenylketonuria with Relevance to Follow-Up -- Three Adult Siblings with Mucopolysaccharidosis Type II (Hunter Syndrome): A Report on Clinical Heterogeneity and 12 Months of Therapy with Idursulfase --Two Argentinean Siblings with CDG-Ix: A Novel Type of Congenital Disorder of Glycosylation? -- Successful Screening for Gaucher Disease in a High-Prevalence Population in Tabuleiro do Norte (Northeastern Brazil): A Cross-Sectional Study -- Two Cases of Pulmonary Hypertension Associated with Type III Glycogen Storage Disease -- Favorable Long-Term Outcome Following Severe Neonatal Hyperammonemic Coma in a Patient with Argininosuccinate Synthetase Deficiency -- Stroke and Stroke-Like Symptoms in Patients with Mutations in the POLG1 Gene -- Perioperative Management of Hemostasis for Surgery of Benign Hepatic Adenomas in Patients with Glycogen Storage Disease Type Ia -- Newborn Screening for Tyrosinemia Type I: Further Evidence that Succinylacetone Determination on Blood Spot Is Essential -- Utility of Rare Disease Registries in Latin America -- The Molecular Landscape of Phosphomannose Mutase Deficiency in Iberian Peninsula: Identification of 15 Population-Specific Mutations -- Quantitative Analysis of mtDNA Content in Formalin-Fixed Paraffin-Embedded Muscle Tissue -- Relevance of Expanded Neonatal Screening of Medium-Chain Acyl Co-A Dehydrogenase Deficiency: Outcome of a Decade in Galicia (Spain)
Electronic reproduction.
Keywords: Metabolism, Inborn errors of -- Case studies; Metabolism, Inborn errors of -- Research; Electronic books